2015
DOI: 10.1017/neu.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-training modafinil administration in a discriminative avoidance task in mice

Abstract: Modafinil impaired memory consolidation in a dose- and time-dependent fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…There were some trends towards decreased rearing behaviour in the central part of the arena in the prenatally exposed mice but this profile was not shown in all measurements. This is in accordance with a study where modafinil dose range 32, 64 and 128 mg/kg did not alter elevated plus behaviour (Fernandes et al 2015). In clinical studies, only modafinil overdose was shown to be anxiogenic (Spiller et al 2009, Carstairs et al 2010 while clinically relevant dose in healthy volunteers lead to improved mood and no anxiety (Taneja et al 2007).…”
Section: Discussionsupporting
confidence: 90%
“…There were some trends towards decreased rearing behaviour in the central part of the arena in the prenatally exposed mice but this profile was not shown in all measurements. This is in accordance with a study where modafinil dose range 32, 64 and 128 mg/kg did not alter elevated plus behaviour (Fernandes et al 2015). In clinical studies, only modafinil overdose was shown to be anxiogenic (Spiller et al 2009, Carstairs et al 2010 while clinically relevant dose in healthy volunteers lead to improved mood and no anxiety (Taneja et al 2007).…”
Section: Discussionsupporting
confidence: 90%
“…However, to prevent overstating the importance of our results, it is necessary to note, that in our study the absolute differences in values were very small (albeit significant). Interestingly, there is also a study with an opposite outcome where modafinil dose range 32, 64 and 128 mg/kg did not alter elevated plus behaviour (Fernandes et al, 2015) and also our own data indicate this design may not capture the anxiogenic effect (Ruda‐Kucerova et al, 2017).…”
Section: Discussionmentioning
confidence: 76%